Strategi Pengembangan Wisata Pantai Labuhan Haji di Kabupaten Lombok Timur - , APRILIA SUSAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Labuhan Haji beach is a tourist destination which is located in East Lombok. The main problem at this beach is rubbish still often found around the coast. The lack of public understanding about the village of Labuhan Haji tourism awareness. Labuan Haji potential as a tourist destination in East Lombok coast has not developed to the maximum by the manager. This study aims to determine the potential for tourism development strategy Labuhan Haji Beach is the SWOT analysis in accordance with the wishes of the beach owned, vision and mission development, recommend adding tourist attractions and infrastructure in Coastal East Lombok Labuhan Haji. The method used was a qualitative method with a through and comprehensive approach or use metode with literature data collection using the desired data based on written evidence, field observations and interviews with local peoples, resource associated with the object. Labuhan Haji beach tourism potential is still hidden and tend to be ignored by the manager. Labuhan Haji society it self can actually with be good cooperative, if the figure can embrace their cadres to this coastal tourism development. The lack of human resources who are experts in the field of development of coastal tourism is one of the problems that exist so that the necessary strategy to solve the problem. With good management strategy will result in a potential tourist destination and does not lose its existence with other attractions that are more developed that has particularly potensin same even better. Tourism activities that can be enjoyed at the beach Labuhan Haji ie swimming, fishing, rowing, sailing, sunbathing, beach volley ball, beach cycling or touring use Cidomo (Cikar Dokar Motor). Amenitas present the hotel or inn, restaurant, Rest Area (Gazebo), restrooms, parking places, health centers. Amenitas improvements and additions to existing facilities necessary to increase the attractiveness of the East Coast's Lombok Labuhan Haji.